Structure-feature relationship of nuclear receptors and fluorescent proteins - Huang, Mian (Kansas State University, 2022)
The protein structure-feature relationship describes how the three-dimensional structure of a protein impacts its feature. The structure-feature relationship of a fluorescent protein (FP) and two nuclear receptors (NRs) were explored in this work. Residues noncovalently interacting with chromophores noticeably impact FP spectra features, but the effects of residues distant from chromophores have not been rigorously characterized. To understand these long-range effects, an FP called darkmRuby was derived from mRuby3 by mutating residues distant from the chromophore. darkmRuby shows dim and bell-shaped pH-dependent fluorescence different from mRuby3. darkmRuby was crystallized at pH 5.0, 8.0, and 9.0. The in silico analysis of the crystal models and site-directed mutagenesis of darkmRuby identify a long-range interaction responsible for its unusual features. Met94 and Phe96 regulate the conformation of His197, adjacent to the chromophore, over 15 Å, mediated by water molecules in a channel. The channel links the chromophore and His197 to external solvent, allowing water molecules to quench fluorescence and poor brightness. The solvent exposure also affects the His197 protonation state, resulting in pH sensitivity. This study provides the first detailed mechanism for long-range effects in FPs. This study extends the mechanistic understanding of FPs and empowers the rational design of new FP biosensors. Human NR RORɣ is the master transcription factor of cytokine IL-17 in T helper 17 cells. Since the overexpression of IL-17 can lead to various autoimmune disorders, RORɣ has drawn attention as a potential drug target. In this project, we selected 15 compounds by computer methods for their potential for binding RORɣ and tested them by differential scanning fluorimetry (DSF). One compound, RG14-2, shows strong binding against the RORɣ ligand-binding domain (LBD). A reporter gene assay showed it inhibited RORɣ transcriptional activity with an IC₅₀ value of 1.5 µM. NMR experiments determined a moderate binding affinity of RG14-2 against the LBD with a K[subscript d] value of 5.7 µM. The co-crystal structure of the RG14-2-bound LBD demonstrates an atomic mechanism for how RG14-2 inhibits the RORɣ transcriptional function. RG14-2 is a promising lead compound for developing a novel class of RORɣ inverse agonists. Breast cancer ranks as the second highest cause of death among cancers in women. About 70% of the cases are ERα-positive (ERα⁺), making the NR ERα an ideal drug target for treating breast cancer. Unfortunately, almost half of the patients carrying ERα⁺ breast cancer develop drug resistance caused by mutations in ERα. In this project, I targeted the most aggressive mutant, Y537S, and attempted to discover new ERα modulators defeating Y537S-mediated drug resistance. A virtual screening workflow was designed to select potential modulators from millions of small molecules. Five top-ranking compounds were chosen and tested by DSF. One compound, ERA1, binds tightly against both the wild-type ERα and the Y537S mutant, showing its potential as a lead compound to develop into a new generation of ERα modulators.
Keywords: Structure-feature relationship; Nuclear receptor; Retinoic acid receptor-related orphan receptor γ; Estrogen receptor α; Fluorescent protein; darkmRuby